2015
DOI: 10.1615/plasmamed.2016015750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flowing Mist Relative Humidity on the Electric Characteristics of Helium Dielectric Barrier Discharge

Abstract: To examine the effect of humidity on the operation of dielectric barrier dis-tween two parallel plates covered by dielectric in water mist. With increasing relative humidity (RH) levels, the signal current indicated different behaviors of the discharge. The discharge began as a multipeak Townsend discharge at low humidity levels. After increasing RH of the injected mist, the width and amplitude of current microdischarges decreased until they reached a diffuse discharge free from microdischarges. With discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Experimental results showed that humidity decreased the discharge frequency and increased the discharge voltage (figures 1(c) and (d)). However, the reduction in current and the increase in voltage resulted in a similar power consumption for both conditions [32][33][34]. The increase in humidity made a greater impact on the chemical properties of plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results showed that humidity decreased the discharge frequency and increased the discharge voltage (figures 1(c) and (d)). However, the reduction in current and the increase in voltage resulted in a similar power consumption for both conditions [32][33][34]. The increase in humidity made a greater impact on the chemical properties of plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Humidity influences the electrical characteristics, the production of reactive species, and the antimicrobial efficacy of non-thermal plasma [26][27][28][29][30][31]. It is well known that water vapor inside a dielectric barrier discharge (DBD) reactor reduces the surface resistance of the dielectric and decreases the discharge current [32][33][34]. Accordingly, the ozone and atomic oxygen density in the plasma phase decreases as humidity increases.…”
Section: Introductionmentioning
confidence: 99%